DAKWAH DAN MASALAH KONTEMPORER - Syafriwaldi Syafriwaldi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
In the science and technology currently, also the success development have penetrated all aspects of the field of life, it is not only bringing the convenience and happiness, but also to new behaviors and issues. There are many issues that long time ago was never known, never imagined; now they are true. this reality is meant by contemporary issues. During this time the theme and scope of da'wah only revolves around the problems of hablum minallah (vertical relationship), or in akhhrawi problem; Syahadat, prayer, fasting, hajj and other religious ritual themes. While the theme of other Islamic da'wah, namely hablum minannas (horizontal relationship) is not much touched on, when in fact the scope or theme of da'wah is very broad. Issues of the ummah's interests are part of the themes of Islamic da'wah, such as democracy, the problem of increasing the resources of the ummah, the problem of economic improvement, work ethic and others. They are rarely alluded in the subject of da'wah material so that da'wah seems not to stand on the earth but in the air.